2001
DOI: 10.1023/a:1008336732273
|View full text |Cite
|
Sign up to set email alerts
|

Temozolomide as a second-line systemic regimen in recurrent high-grade glioma: A phase II study

Abstract: On multivariate analysis, response to previous treatment was significant (P = 0.03) for time to progression and Karnofsky performance score for overall survivall (P = 0.002). Temozolomide gave a moderate response rate with acceptable toxicity as second-line chemotherapy in patients with recurrent high-grade glioma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
37
0
2

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(43 citation statements)
references
References 8 publications
4
37
0
2
Order By: Relevance
“…Not only oligodendroglial tumours respond to TMZ, as was demonstrated by Yung et al (1999), who reported a response rate of 35% and disease stabilisation in 26% of their series of predominantly anaplastic astrocytoma. These response rates are higher as compared with our results that are more comparable with the response rates of 11 and 23%, respectively as observed in other phase II trials in high-grade glioma (Bower et al, 1997;Brandes et al, 2001). Even if the reported response rates of the various clinical trials are not homogeneously high, we must consider that TMZ is one of the few drugs that have shown activity as single drug in high-grade glioma.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Not only oligodendroglial tumours respond to TMZ, as was demonstrated by Yung et al (1999), who reported a response rate of 35% and disease stabilisation in 26% of their series of predominantly anaplastic astrocytoma. These response rates are higher as compared with our results that are more comparable with the response rates of 11 and 23%, respectively as observed in other phase II trials in high-grade glioma (Bower et al, 1997;Brandes et al, 2001). Even if the reported response rates of the various clinical trials are not homogeneously high, we must consider that TMZ is one of the few drugs that have shown activity as single drug in high-grade glioma.…”
Section: Discussionsupporting
confidence: 79%
“…In children, the MTD is 180 mg m À2 day À1 for patients with previous CSI (Nicholson et al, 1998) and 200 -215 mg m À2 day À1 , respectively for patients without prior CSI (Estlin et al, 1998;Nicholson et al, 1998, respectively). The reports of phase II trials of TMZ using comparable administration regimens of 150 -200 mg m À2 day À1 Â 5 every 28 days in adults with recurrent or progressive grade III or grade IV (oligodendro-) glioma showed objective response rates varying from 8, 11, 23, 35 and 44%, respectively (Brada et al, 2001;Bower et al, 1997;Brandes et al, 2001;Yung et al, 1999;Chinot et al, 2001, respectively). A phase II clinical trial by the UKCCSG New Agents Group/SFOP 'Groupe de Pharmacologie' with this regimen of TMZ in paediatric patients with recurrent or progressive high-grade glioma showed a lower response rate of 12% for supratentorial high-grade glioma and 6% for brainstem glioma, respectively (Lashford et al, 2002).…”
mentioning
confidence: 99%
“…Both trials used a schedule of TMZ 150-200 mg/m 2 for 5 out of 28 days. Other prospective studies mainly without previous TMZ treatment using this schedule showed similar PFS-6 rates ranging from 21 to 24% [64][65][66][67].…”
Section: Temozolomide Monotherapy and Combination Regimensmentioning
confidence: 54%
“…11,12 In a few studies, patients who received previous therapy with nitrosoureas remained at the 150 mg/m 2 per day dose and responses at this lower dose have been reported. 22 Overall, this regimen was reasonably well tolerated. Most of the serious study drug-related toxicities were hematologic or infectious.…”
Section: Discussionmentioning
confidence: 85%